The Impact of Pulsatile Flow on Suspension Force for Hydrodynamically Levitated Blood Pump. (3rd June 2019) - Fu, Yang; Hu, Yimin; Huang, Feng; Zhou, Maoying
Abstract : Hydrodynamically levitated rotary blood pumps (RBPs) with noncontact bearing are effective to enhance the blood compatibility. The spiral groove bearing (SGB) is one of the key components which offer the suspension force to the RBP. Current studies focus on the suspension performance of the SGB under continuous flow condition. However, the RBP shows pulsatile characteristics in the actual clinical application, which may affect the suspension performance of the SGB. In this paper, the impact of pulsatile flow upon the suspension force from the SGB is studied. A model of the SGB with a groove formed of wedge-shaped spirals is built. Then, the CFD calculation of the hydrodynamic force offered by designed SGB under simulated pulsatile flow is introduced to obtain the pulsatile performance of the suspension force. The proposed method was validated by experiments measuring the hydrodynamic force with different bearing gaps. The results show that the suspension force of the SGB under pulsate flow is the same as under steady flow with equivalent effective pressure. This paper provides a method for suspension performance test of the SGB.